Soft magnetic properties of MnZn ferrites prepared by powder injection moulding - Mitrović N.S. (Science of Sintering, 2012)
In this study, properties of soft-magnetic manganese zinc ferrite manufactured by powder injection moulding - PIM technology were presented. A powder consisting of Mn1- xZnxFe2O4 with small addition of hematite □-Fe2O3 was mixed with an organic binder (wax and thermoplastic) to form ferrite feedstock. The ferrite feedstock was injected in a mould with a cavity shaped like a small cylinder with a hole on the main axis. Injection moulded samples were then solvent, thermally debinded and sintered in air atmosphere. Structure of sintered sample was characterized using X-ray diffractometry, scanning electron microscopy and thermomagnetic measurements. Magnetic properties were measured by hysteresis graph at different frequencies up to 1 kHz. Sintered sample contains a mixture of two phases Mn0.6Zn0.4Fe2O4 (68 wt. %) and α-Fe2O3 (32 wt. %). The Curie temperature is TC ≈ 220°C for the green sample but after the heating up to 470°C, TC increase up to about 300°C. The high increase of normalized magnetic permeability of about 800 % was observed due to melting and burning of binder. The hysteresis loop of sintered MnZn ferrite toroidal cores has an R-shape with saturation of 0.44 T and remanence ratio of 0.49. The low value of coercivity (only 47 A/m) was related to the presence of α-Fe2O3 crystalline phase and attained already optimum density (ρ ≈ 4.8 g/cm³) i.e. observed low level of porosity. Attained relative magnetic permeability μr ≈ 2000 as well as power losses Ps ≈ 21 W/kg for sintered sample (at 1 kHz; 0.39 T) is in agreement with the MnZn ferrite commercial samples. [Projekat Ministarstva nauke Republike Srbije, br. OI 172057]